Isıtma Araçlarının Gelişimi Ve Elektrikli Bir Isıtma Aracının Belirli Gereksinimlere Göre Tasarlanması - Altuğ, Hülya (Fen Bilimleri Enstitüsü, 1994)
İnsanoğlu varlığının başladığı dönemden itibaren aklı yardımı ile, fiziksel özelliklerinin çevre koşullarına uymadığı durumlarda çeşitli çareler bulmayı başarmıştır. Isınma da bunlardan biridir. Bu çalışmada insanın tarih boyunca ısınmak için icat etmiş olduğu araçlar, tarih içindeki yerleri, sosyal ve teknik yönleri ile ele alınmış, faydalan ya da zararları değerlendirilerek ve dönemleri de göz önünde bulundurularak aralarında kıyaslamalar yapılmış, bunlardan birisinin ise projelendirilmesi ve bir prototip üretimi sağlanmıştır. Çalışmanın birinci bölümünde; günümüz ve çevremiz koşullarına uygun olarak tasarlanan bir aracın amaçları ve bu araca yaklaşım açıklanmaktadır. Ayrıca insan oğlunun ilk ısınma yöntemi olarak ateşi bulması, bu olayın hangi bölgelerde başladığı ve ne şekilde kullanıldığı antropolojik bulgulara dayanılarak anlatılmaktadır. ikinci bölümde; ısınmaya ilişkin olarak çağdaş insanın ısınması ve ısıtma sistemleri üzerine genel görüşler ortaya konmaktadır. Üçüncü bölümde; geçmişten günümüze tüm ısıtma sistemleri, bireysel ve merkezi olarak ve enerji kaynaklarına göre sınıflandırılarak ele alınmakta, tarifi yapılmakta ve çok yönlü olarak değerlendirilmektedir. Dördüncü bölümde; örnek alan olarak seçilen İstanbul' da yaşamakta olan belli yaş ve sosyal gruplara ait insanlara uygulanan bir anket araştırması bulunmaktadır. Bu araştırmada insanların ısınma alışkanlıkları, gereksinmeleri ve projelendirilip bir prototipi imal edilmesi düşünülen elektrikli ısıtma aracını kullanmaya yatkınlıkları saptanmaya çalışılmış ve projelendirme gerçekleştirilmiştir. Beşinci bölümde ise; tezin amacına ne derecede ulaşıldığı tartışılmaktadır.

Man has tried to find solutions to problems arising from his struggle to adapt the physical conditions surrounding him, which may sometimes be unfavorable. In this study, the history of methods which man has used to heat himself, including the related social and technical aspects, was presented; the advantages and the disadvantages of contemporaneous methods of heating were compared; and a prototype of a heater based on one of the discussed techniques was designed and constructed. The first section of this study deals with its aim. Man has used various methods for heating, depending on the structure of his society and the physical conditions of his millleu.Among these methods, central heating (CH) has appeared as the most rational and the convenient. Nevertheless, there is still a considerable demand for local heaters (LHs) in many countries, including Türkiye. LHs utilizing electricity have been considered as the most practical, convenient, and the safest. The aim of this study was to design and construct an electrical LH using a resistance for the generation of heat which also includes an electrical cookstove. A survey held on some residents in Istanbul demostrated that CH was preferred most, but LHs were demanded as well. This survey also showed that those LHs utilizing eletricity were considered as the most convenient and the safest. The second section of this study tells how man discovered fire and utilized it in prehistorical times. Catastrophs such as volcanic eruptions and forest fires were the first events which introduced man to fire. In time, he was able to control fire and used it for his comfort such as heating himself. Gradually, fire found use in all societies. The oldest X evidence on the use of fire by man came from the findings of some excavations in North China. These findings suggested that man was able to use fire, but not to put it up at that time. Since then, his efforts to warm himself led to a number of discoveries which constitutes the history of heaters. Each successive discovery led the path to greater comfort and perfection. In the third section of this study, various metfaos of heating were compared. The optimal indoor temperature, which depends on the climate and the outdoor temperature was determined. The maintenance of such a temperature will optimize man's efficiency. Nevertheless, the optimal temperature should be maintained without comprimising the quality of the indoor air. The current technology which satisfy these requirements is CH. First, a single boiler is used for CH whereas a number of heaters are required to heat each compartment locally; second, CH consumes less fuel to heat a given space as compared with LHs; third, radiators, which are parts of a CH system, occupy less space than all LHs used to heat a given space; and last, CH is more cost-effective than heating locally, in particular, large spaces, as circulation of warm air with the former is better. Inspite of these advantages of CH over LHs, there is still a demand for the latter in cetain circumstances, e.g., when CH breaks down; when the building in which CF is to be installed is historical, and such an installment would damage the building; or when economical constrains do not permit the installment of CH. In the fourth section, the heating systems which have been commonly used in the present and in the past were evaluated. LHs, which include a variety of historical and modern forms, generate heat in their bodies and warms local surroundings. In CH, heat generated in a boiler is transported via pipes to radiators, each of which warms local surroundings. CH systems vary depending on their operational characteristics and the types of fuel they utilize, but all function according to the same aforementioned principle. Fireplaces, which are still in use in certain places of the world, are the most ancient and primitive LHs. Although they are no longer considered as adequate main heat generators, they have left unerasable marks in the history of mankind. A typical fireplace consists of two parts: the fireplace itself and the chimney. The interior of the XI fireplace consists of a central piece, afire hood, a funnel and sides. The chimney is constructed as an optimal outlet for the fumes. The stove is the simplest LH. Fuel is burnt in a small chamber, minimizing heat losses and its exterior metal cover radiates heat to the surrounding. Although those that burn coal are used most often, other types which burn wood, fuel oil and diesel oil exist. Improvements in their design have increased their effiency. A patent exhaust is critical for their fuction. Although electricity alone is not a type of fuel, it is an energy source which can be tranformed to heat with the help of an apparatus. The ease with which it can be divided and distributed is another advantage as an energy supply for the heater. Thre are several types of electrical LHs: Iron radiators filled with oil use an electrical resistance to generate heat They are suitable for prolonged heating and consume 750- 1000 W. Some contain thermostates, and rollers on which they can be transported. Heat accumulators became popular during the petrol crisis. These devices accumulate heat during the night, and release it during the day. They contain elements consisting of magnesium, which can accumulate heat and stand high temperatures. The heat accumulators are of two types: one type radiates heat while the other convects it with the help of a fan. Because of their large size and weight as well as the noise produced by the fan, they are no longer prefered. A radiation heater is a device that radiates infrared light from a point to its surrounding, or a panel which is composed of a electrical resistance embedded in a quartz case that is placed in front of a steel plaque. Their energy consumption varies between 500W and 2000W. Convector heaters use an electrical resistance embedded in a metal case within which air circulation is maintained. They are attached on the wall and grouped into two depending on their thickness: the 'standard' ones are 10-13 cm thick while the 'extra- flat' ones are only 4 cm in their thickness. Their energy consumption varies between 500W and 3000W. They are equipped with thermostates. A fan added to such heaters helps to speed up warming of the space homogeniously. They can also be embedded in the floor, eliminating loss of space, but such an application requires XII specialized personnel who can do the installation. They can also be designed as plinth in which case a space can be son-rounded by alternating heating and non-heating modulary pieces which look identical, creating a visual continuity. Such models consume 400-500W/m. Electrical resistances can also embedded in a supporting material that is not thick, e.g., wall or floor cover, creating a surface temperature of 25°C to 30° C at a consuptionof 150-200W/m2. Heaters burning gasoline can be modulary, i.e., each radiator fuctions independently. In this system, each radiator contains a combustion unit and a thermostate. Gasoline is sucked by an automatic apparatus to the combustion unit of the radiator from the main reservoir via metal pipes. Because they offer rapid and efficient heating, they are often employed in secondary spaces or during the turn of seasons when CH is not in use, but the weather temperature necessicates heating, at least during a part of the day. Such heating systems should be maintained by specialized personnel. Electric and gasoline heaters also have mobile models which move on rollers. These models are not made to fix. Today, heaters utilizing infrared light and liquid gas such as butane are used more often. They are usually equipped with a piezo-electrical ignition system. Although the first applications of CH dates back to the Roman Empire era, this method became popular in the 1 9th century following the immergence of the bourgeoisie. At present, it is the most preferred method for heating houses. The function of CH is based on transporting water that is heated in a boiler to radiators via pipes. Some models use air instead of water for transporting heat. This system can only be installed in buildings that are newly constructed, and such an installation requires specialized personnel. Electrical heaters embedded in the floor is another CH system. The embedment should be done as the cement is being laid on the floor. A variety of energy sources can be utilized for CH. Among these, coal has long been used, but is not recommened any longer. Although wood was rarely used xm in the past, its derivatives has found a greater use as fuel for CH today. The amount of fuel (wood and its derivatives) to be burnt can be adjusted and fed to the boiler automaticly using a special apparatus. Advances in the CH technology has lead to the replacement of coal by fuel- oil which became the most popular energy source for CH in the sixties. Nevertheless, other energy sources such as gas, electric, and polycombination products has appeared as competitors during the "petrol crisis" and thereafter. Liquid petrolium gas (LPG) has started to replace natural gas as an energy source for CH in Europe. In areas where LPG cannot be transported, propane can be used instead. In CH systems utilizing gas, fumes should be expelled with a suction system. Otherwise, the apparatus used in such types of CH systems is identical to the conventional ones. Convectors, although not popular, can be used to heat rooms that are not used regularly. They are designed to create an air circulation.
Evolution Of Heaters And Designing A Heating Device For Specific Needs
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1994
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1994
Keywords: Elektrik enerjisi; Isınma; Isıtma araçları; Electrical energy; Warming Heaters